The Protective Role of Tanshinone IIA in Silicosis Rat Model via TGF-β1/Smad Signaling Suppression, NOX4 Inhibition and Nrf2/ARE Signaling Activation - Feng F; Cheng P; Zhang H; Li N; Qi Y; Wang H; Wang Y; Wang W (Dove Medical Press, 2019)
Feifei Feng,1 Peng Cheng,2 Huanan Zhang,1 Nannan Li,1 Yuxin Qi,3 Hui Wang,1 Yongbin Wang,1 Wei Wang1 1Department of Respiratory Medicine, The Second Hospital of Shandong University, Jinan, Shandong 250033, People’s Republic of China; 2Department of Neural Medicine, The Second Hospital of Shandong University, Jinan, Shandong 250033, People’s Republic of China; 3Department of Respiratory Medicine, Jinan People’s Hospital, Jinan, Shandong 250033, People’s Republic of ChinaCorrespondence: Wei WangDepartment of Respiratory Medicine, The Second Hospital of Shandong University, 247 Beiyuan Street, Jinan, Shandong 250033, People’s Republic of ChinaTel +86 17660080618Email sducp@qq.comPurpose: Silicosis is an occupational disease caused by inhalation of silica and there are no effective drugs to treat this disease. Tanshinone IIA (Tan IIA), a traditional natural component, has been reported to possess anti-inflammatory, antioxidant, and anti-fibrotic properties. The current study’s purpose was to examine Tan IIA’s protective effects against silica-induced pulmonary fibrosis and to explore the underlying mechanisms.Methods: 48 male SD rats were randomly divided into four groups (n=12): i) Control group; ii) Silicosis group; iii) Tan IIA group; iv) Silicosis +Tan IIA group. Two days after modeling, the rats of Tan IIA group and Silicosis +Tan IIA group were given intraperitoneal administration 25 mg/kg/d Tan IIA for 40 days. Then, the four groups of rats were sacrificed and the lung inflammatory responses were measured by ELISA, lung damage and fibrosis were analyzed by hematoxylin and eosin (H&E) staining and Masson staining, the expression levels of collagen I, fibronectin and α-smooth muscle actin (α-SMA) were measured by immunohistochemistry. The markers of oxidative stress were measured by commercial kits, and the activity of the TGF-β1/Smad and NOX4, Nrf2/ARE signaling pathways were measured by RT-PCR and Western blotting.Results: The silica-induced pulmonary inflammtory responses, structural damage and fibrosis were significantly attenuated by Tan IIA treatment. In addition, treatment with Tan IIA decreased collagen I, fibronectin and α-SMA expression, and inhibited TGF-β1/Smad signaling in the lung tissue. The upregulated levels of oxidative stress markers in silicosis rats were also markedly restored following Tan IIA treatment. Furthermore, treatment with Tan IIA reduced NOX4 expression and enhanced activation of the Nrf2/ARE pathway in the lung tissue of silicosis rats.Conclusion: These findings suggest that Tan IIA may protect lung from silica damage via the suppression of TGF-β1/Smad signaling, inhibition of NOX4 expression and activation of the Nrf2/ARE pathway.Keywords: silicosis, tanshinone IIA, TGF-β1/Smad, NOX4, Nrf2/ARE